Application of laserspeckleinterferometry to fracture mechanical investigations of bonds and non homogeneous materials - Junghans, Eva (Kovine zlitine tehnologije, 1999)
With commonly used test procedures, like measuring the average displacement with clip-gauges or measuring displacement quantitatively with field measuring techniques over a selected specimen surface, only limited information can be obtained for a welded joint. Therefore the influence of notch position and weld geometry on deformation initiation and further deformation is not sufficently well known. As a censequence, an enhanced defect assessment of welded components is not possible. Due to recent developments in field-measurement techniques, in computer technology and specific programs it is now possible to obtain detailed information about the quantitative deformation in base and weld metal in an effective and economic manner. In this contribution the analysis with laserspeckleinterferometry is described. Furthermore, computer-assisted laserspeckleinterferometry is applied to SENT specimens with different notch positions in the higher strength weld metal. With laserspeckleinterferometry the quantitative deformation performed in base and weld metal under the influence of the 45°-yielding starting from the crack tip, was measured. The possible evaluation for laserspeckleinterferomerty in terms of total deformation, partial deformation and deformation perfoprmed during single steps of the experiment are demonstrated. From the results the influence of notch position and weld geometry on the deformation behaviour could be evaluated. The consequences for the analytical determinataion of the yield load for welded joints, as input for defect assessment, are derived.
Keywords: preizkušanje; lomna mehanika; laserspeckleinterferometrija; zvari